Co3O4-γ-Fe2O3 Nanocrystal Heterostructures with Enhanced Coercivity and Blocking Temperature - Nethravathi, C.; Rajamathi, Catherine R.; Caron, Luana; Kalache, Adel; Machado, Jyothi; Rajamathi, Michael; Felser, Claudia (Journal of Physical Chemistry C, 2020)
Reassembly of α-cobalt hydroxide nanosheets in the presence of citrate-capped γ-Fe2O3 nanoparticles yields α-cobalt hydroxide-γ-Fe2O3 hybrid in which the nanoparticles are trapped between the nanosheets. Thermal decomposition of the hybrid yields the Co3O4-γ-Fe2O3 heterostructure. While the saturation magnetization (Ms) of γ-Fe2O3 is preserved in the Co3O4-γ-Fe2O3 heterostructure, the interface between the oxides in the heterostructure enhances the coercive field (HC) to a large extent. The coercivity persists even above the Néel temperature of Co3O4 with the blocking temperature increased beyond room temperature. The unique morphology of the heterostructure wherein the Co3O4 and γ-Fe2O3 particles are fused together to form a larger network leading to strong interparticle interactions, diffusion of Co atoms into the surface of γ-Fe2O3 particles, and strain at the interfaces appear to be the reasons behind the improved magnetic behavior.
CRIS-Team Scopus Importer:2022-04-14